2006
DOI: 10.1353/psc.2005.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water Removal on a Hawaiian Stream Ecosystem

Abstract: A 3-year study of Wainiha River on Kaua'i, Hawai'i, was carried out to determine the impact that water removal had on key stream ecosystem parameters and functions. The study area included a diversion dam for a hydroelectric plant that removes water at an elevation of 213 m and returns it to the stream about 6 km downstream at an elevation of 30 m. There were two highelevation sites, one with undiverted flow and one with reduced flow, and two low-elevation sites, one with reduced flow and one with full flow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 71 publications
(66 reference statements)
1
19
0
Order By: Relevance
“…Dudgeon (1992) reported declines in macroinvertebrate species richness and changes in the densities of several taxa in a stream in Hong Kong when flow ceased during the dry season because of abstraction at an upstream weir. And Kinzie et al (2006) found that macroinvertebrate density and biomass density were lower downstream than upstream of a point on a Hawaiian stream where all surface flow was diverted during low-flow periods. Even with diversion of very large proportions of flow, apparent impacts are not necessarily detected in all assessed attributes of macroinvertebrate assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Dudgeon (1992) reported declines in macroinvertebrate species richness and changes in the densities of several taxa in a stream in Hong Kong when flow ceased during the dry season because of abstraction at an upstream weir. And Kinzie et al (2006) found that macroinvertebrate density and biomass density were lower downstream than upstream of a point on a Hawaiian stream where all surface flow was diverted during low-flow periods. Even with diversion of very large proportions of flow, apparent impacts are not necessarily detected in all assessed attributes of macroinvertebrate assemblages.…”
Section: Discussionmentioning
confidence: 99%
“…Declines in taxonomic diversity are commonly observed in benthic macroinvertebrate communities in reduced flow reaches (Cazaubon and Giudicelli, 1999;McIntosh et al, 2002;Kinzie et al, 2006). The decrease in water volume results in habitat loss and a decrease in the quantity and quality of food, leading to the disappearance of some taxa (McKay and King, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In river reaches with reduced flows, it is common to detect declines in density, diversity through the disappearance of taxa susceptible to flow regime changes (McIntosh et al, 2002;Kinzie et al, 2006). Disturbances may consequently affect ecological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The strong decline in scraper's density to a quarter of pre-disturbed densities cannot be attributed to reductions in benthic algae, as flow reduction can have a general opposite effect on algae richness (Biggs and Smith, 2002;Dewson et al, 2007), but can be deleterious if water reduction is severe (Kinzie et al, 2006). Water reduction did not result in stream drying, and the short-term duration of the study may have precluded significant damage to algae, as we observed oxygen maxima over control values at Caselas drought stretch supporting the existence of active biofilms during flow reduction.…”
Section: Trait Level Impactsmentioning
confidence: 99%